2017
DOI: 10.1124/dmd.116.074740
|View full text |Cite
|
Sign up to set email alerts
|

Coproporphyrin-I: A Fluorescent, Endogenous Optimal Probe Substrate for ABCC2 (MRP2) Suitable for Vesicle-Based MRP2 Inhibition Assay

Abstract: Inside-out-oriented membrane vesicles are useful tools to investigate whether a compound can be an inhibitor of efflux transporters such as multidrug resistance-associated protein 2 (MRP2). However, because of technical limitations of substrate diffusion and low dynamic uptake windows for interacting drugs used in the clinic, estradiol-17-glucuronide (E17G) remains the probe substrate that is frequently used in MRP2 inhibition assays. Here we recapitulated the sigmoidal kinetics of MRP2-mediated transport of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 29 publications
(35 reference statements)
1
56
0
Order By: Relevance
“…Consequently, the Ki obtained by modeling of clinical data reflects RIF inhibition of OATP1B‐mediated transport of CPI. It is important to note that recent studies suggest that CPI is also a substrate for MRP2 and its transport is inhibited by RIF, with an IC 50 of 83 μM . Considering a previously reported RIF unbound liver‐to‐plasma concentration ratio of 3.3 in humans and that maximum unbound plasma concentration observed here was >25 times lower than the MRP2 IC 50 , the impact of this interaction on CPI systemic exposure is expected to be negligible.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Consequently, the Ki obtained by modeling of clinical data reflects RIF inhibition of OATP1B‐mediated transport of CPI. It is important to note that recent studies suggest that CPI is also a substrate for MRP2 and its transport is inhibited by RIF, with an IC 50 of 83 μM . Considering a previously reported RIF unbound liver‐to‐plasma concentration ratio of 3.3 in humans and that maximum unbound plasma concentration observed here was >25 times lower than the MRP2 IC 50 , the impact of this interaction on CPI systemic exposure is expected to be negligible.…”
Section: Discussionmentioning
confidence: 60%
“…The simulation was based on a two period one‐way crossover study design where in the first period plasma/urine samples of CPI are observed under baseline condition and following a period of washout the same subjects received a single dose of 600 mg RIF and plasma/urine samples of CPI were collected again for analysis. Power curves were calculated for each modified I/Ki ratio by performing a one‐sample paired t ‐test on the ratio of logarithmic transformed AUC following simulation at predefined sample sizes . At each sample size, the simulation and tests were repeated 5,000 times and the power of the test was calculated as the proportion of the simulations during which the null hypothesis was rejected at the significance level (0.05 and 0.01).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we aimed to establish a PBPK model for CP‐I in which hepatic uptake and efflux processes are considered. Followed by hepatic uptake, CP‐I undergoes biliary excretion via multidrug resistance‐associated protein 2 (MRP2) . Clinical data, obtained with the positron emission tomography probe [ 11 C]‐TIC‐Me, has shown that MRP2‐mediated biliary excretion can be significantly inhibited by RIF at a clinically relevant dose (600 mg).…”
mentioning
confidence: 99%
“…Followed by hepatic uptake, CP-I undergoes biliary excretion 14 via multidrug resistance-associated protein 2 (MRP2). 15 Clinical data, obtained with the positron emission tomography probe [ 11 C]-TIC-Me, has shown that MRP2-mediated biliary excretion 16 can be significantly inhibited by RIF at a clinically relevant dose (600 mg). Such data suggest the DDI potential of RIF against MRP2, 17 but in vitro inhibition data can be problematic because of the high variability in the reported values of in vitro inhibition constants (K i ) for MRP2 (7.9-83 μM, as listed in the University of Washington Metabolism and Transport Drug Interaction Database).…”
mentioning
confidence: 99%
“…In the IOVs the cytoplasmic ATP-binding domain and the substrate binding site of the efflux transporter are on the outside of the membrane bilayer and consequently the ATP-dependent uptake of a substrate by IOV in vitro corresponds to its in vivo efflux by the transporter protein [23]. Recently, Gilibili et al, pointed out several limitations including extensive substrate diffusion into membrane vesicles and the lack of an optimal dynamic window of ATP-dependent uptake that makes this in vitro vesicle assay unsuitable for many substrates [24]. In our case, pravastatin is a hydrophilic compound and thus diffuses poorly across membranes.…”
Section: Discussionmentioning
confidence: 99%